Evaluation of nutrient content and antioxidant, neuritogenic, and neuroprotective activities of upland rice bran oil - Ruen-ngam, Duangkamol; Thawai, Chitti; Sukonthamut, Sujitra; Nokkoul, Raumjit; Tadtong, Sarin (My University, 2018)
Upland rice bran is an abundant and valuable antioxidant by-product of rice milling. This study compares the content of γ-oryzanol, γ-tocopherol, and phytochemicals in rice bran oil from 4 varieties of upland rice; Dok-kham (DK), Dok-kha (D), Khem-ngen (KN), and Nang-dam (ND); with that of a conventional variety, Khao Dowk Mali 105 (MA). The extraction was done by shaking rice bran in ethanol in 250 ml flask with a rice bran to a solvent ratio of 1:5 (w/v) at 200 rpm (0.447g) and 30°C in the dark for 30 min. The antioxidant capacity of the extracted oil was evaluated by several methods; DPPH, ferric reducing ability power, and ABTS'+ assays. The colour of upland rice bran oil was dark from its phenolic and flavonoid contents. The highest contents of γ-oryzanol and γ-tocopherol were found in the bran oil from KN. The highest phytochemical content was found in the bran oil from DK. DK provided the highest antioxidant activity among the varieties mentioned. The neuroprotective and neuritogenic effects of rice bran extracts were also evaluated. D and KN extracts were the best two neuroprotective and neuritogenic extracts because they had the highest contents of γ-oryzanol and colour pigments. Thus Thai rice bran oil has the potential to be an excellent food supplement product due to its high antioxidant contents.
Keywords: Antioxidant activity; Phytochemicals